The interactive effects of ketamine and ethanol on dopamine expression in the ventral tegmental area of rats - Zhang ZB (Dove Medical Press, 2018)
Zhi-Bi Zhang,1 Tian-Yong Xu,2 Ding-Yun You,3 Shuai Yi,4 Qing Liu,4 Huifang-Jie Li,4 Jin-Yun Gu5 1Biomedical Engineering Center, Kunming Medical University, Kunming, People’s Republic of China; 2Experiment Center for Medical Science Research, Kunming, People’s Republic of China; 3Department of Science and Technology, Kunming Medical University, Kunming, People’s Republic of China; 4School of Forensic Medicine, Kunming Medical University, Kunming, People’s Republic of China; 5Zhanyi Branch of Qujing Public Security Bureau, Qujing, People’s Republic of China Background: A number of studies have demonstrated the significant and rapid antidepressant effects of ketamine, which is also known as a neurotoxic and illicit drug. Ketamine and alcohol are increasingly used together in clubs by teenagers and young adults. Previous studies have proven that chronic ketamine consumption induces a delayed and persistent activation of the dopamine (DA) system. However, the rewarding properties of recreational ketamine abuse remain unclear, and the underlying mechanisms of the effects on the DA system after administration of ketamine with ethanol are yet to be explored. Methods: Here, we evaluated the effects of two different doses of ketamine (30 mg/kg and 60 mg/kg) with and without ethanol (0.3156 g/kg) on DA concentration in the rat’s ventral tegmental area (VTA), a vital region in the reward and motivation system. We explored the effects of the combined drug treatment on the expression profiling of the DA metabolism genes, tyrosine hydroxylase, dopa decarboxylase, vesicular monoamine transporter 2, and synaptosomal-associated protein 25, as well as protein expression level of brain-derived neurotrophic factor in the rat’s VTA. Results: We found that administration of ketamine with ethanol led to a significant increase of DA in the VTA associated with differential regulation of mRNA levels of the four DA metabolism genes and protein levels of brain-derived neurotrophic factor. Moreover, the rewarding properties of coadministration of ketamine and ethanol were related to dopaminergic neuron activation in the VTA. Conclusion: These results indicated the possibility that combined drug treatment might positively affect the mesencephalic DA reward system. Keywords: ketamine, ethanol, TH, DDC, dopamine, ventral tegmental area